ANTHOCYANIN EXTRACTION FROM RED SPINACH UTILIZING MICROWAVE IRRADIATION AND ITS APPLICATION IN FOOD PRODUCTS - Iriany Iriany; Zuhrina Masyithah; Taslim Taslim; Calvin Calvin; Idham Sahdin Tanjung (JURNAL INTEGRASI PROSES, 2024)
In contemporary times, using food coloring agents is necessary to capture attention. The extensive use of synthetic food coloring agents has raised significant health concerns. Red spinach, a plentiful vegetable in Indonesia, contains anthocyanins that give it a reddish-purple color. The presence of anthocyanins makes red spinach a promising natural coloring agent. This research aims to identify the optimal operational conditions for extracting anthocyanins from red spinach, with the ultimate goal of applying these findings in developing innovative food products. The fixed variables included 20 grams of dried red spinach, a 10-minute extraction duration, and distilled water as the solvent. The independent variables were microwave power levels (100, 300, 500 W) and the material-to-solvent (M/S) ratio (1:10, 1:15 g/mL). The results revealed a moisture content of 7.6% in red spinach. The highest yield was achieved at 100 W with an M/S ratio of 1:15 g/mL, yielding 80%. The best anthocyanin extract was determined based on the highest anthocyanin content, which was obtained at 300 W with an M/S ratio of 1:15 g/mL, resulting in 56.93 mg/L. Anthocyanins were stable at low temperatures (4°C) but highly unstable at high temperatures. Sensory testing to determine consumer acceptability showed no significant taste difference between beverages with added anthocyanin extract and those without. The resulting taste was mild, and the extract's color was appealing. Therefore, the anthocyanin extract from red spinach can be used as a natural coloring agent, replacing hazardous synthetic food colorants.